General Comment No. 36 (2018) on Article 6 of the International Covenant on Civil and Political Rights, on the Right to Life (H.R. Comm.). (August 2019) - Joseph, Sarah
Abstract : In October 2018, the United Nations Human Rights Committee (UNHRC) adopted General Comment 36 on Article 6 of the International Covenant on Civil and Political Rights (ICCPR), the guarantee of the right to life.